THE UGARITIC CULT OF THE DEAD A STUDY OF SOME BELIEFS AND PRACTICES THAT PERTAIN TO THE UGARITIAN'S TREATMENT OF THE DEAD - Angi, Jean Betty (My University, 1971)
This work attempts to deal with the results of the excavations of the tombs at Ras Shamra, and with the Ugaritic literary material that has relevance for the treatment of the dead at Ugarit. The investigation has shown that an important aspect of the religion at Ugarit centred around the reverencing of the family dead.
Keywords: Religion; Religion